Increasing students' critical thinking ability in mathematics and fighting power through the implementation of an Open-Ended Approach - Sari, Intana Purnama; Siregar, Tanti Jumaisyaroh (International Journal of Trends in Mathematics Education Research, 2024)
One of the challenges for teachers in the world of education is to implement programs that can improve critical thinking skills and increase students' fighting power. One way to improve the quality of mathematics education is to use a learning model that supports the realization of the true goals of mathematics education, including improving students' critical thinking skills and fighting power. Therefore, the purpose of this research is to improve students' mathematical critical thinking skills and fighting power through the application of an open-ended approach. The design of this research is Experimental Factorial with the aim of improving critical thinking skills and fighting power. The subject of this study is Class X MAS Nurul Khair. In this study, the data collection tools used include a critical thinking ability test and a fighting force questionnaire. The results of the study are as follows: 1) the improvement of critical thinking skills is better if using the open-ended approach compared to the conventional, 2) the increase in fighting power is better if using the open-ended approach compared to the conventional.